Penilaian HOTS dan Penerapannya di SD/MI - mufa taubah (Sekolah Tinggi Agama Islam Negeri (STAIN) Kudus, 2019)
Abstrack: This research is included in the type of field research by carrying out data mining on subjects at the data source. This study wants to know a description of what is the assessment of learning based on HOTS and how the Application of Assessment of Hots (Higher Order Thinking Skills) in learning in MI (Madrasah Ibtidaiyah). Higher Order Thinking Skill-based assessment is a way of thinking at a higher level than memorizing, or retelling something that is told by others. In the determination needed the ability of teachers. Each subject teacher should be creative in developing HOTS questions in accordance with KI-KD, which are possible in the subjects they teach. Teacher's insight into global issues, skills in choosing stimulus questions, as well as the ability to choose competencies tested, are important aspects that must be considered by teachers, in order to produce quality items. The mistake of understanding the concept of HOTS by the teacher will have an impact on learning model errors that are increasingly ineffective and unproductive.